2009
DOI: 10.1111/j.1365-277x.2009.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of Irish older people in receipt of meals‐on‐wheels and the nutritional content of meals provided

Abstract: Background: Research has suggested that meals-on-wheels recipients can be at risk for poor nutritional status. Despite this, few countries have statutory minimum requirements for the nutrient content of meals-on-wheels. This study examined both the nutritional status of a sample of Irish recipients and the nutrient content of a sample of meals provided to determine whether Irish recipients would benefit from statutory minimum nutritional standards.Methods: The study had two phases. Firstly, a nutritional asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…By supporting the nutritional status of older adults, MOW aims to promote independence and improve quality of life (8). However, studies from Australia and other countries have demonstrated that even with the provision of home-delivered meals, some MOW clients still have poor nutritional status due to their multiple medical and social risk factors (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…By supporting the nutritional status of older adults, MOW aims to promote independence and improve quality of life (8). However, studies from Australia and other countries have demonstrated that even with the provision of home-delivered meals, some MOW clients still have poor nutritional status due to their multiple medical and social risk factors (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In South Australia, approximately 10% of persons aged 65 years or over receive some publically funded home-care service such as MOW. Services like MOW appear, intuitively, vital to assist older persons remain healthy and functionally independent, and while some research has shown that the provision of homedelivered meals improves the nutritional intake of older people [11][12][13], others have reported that the nutritional content of the meals is less than adequate [14,15]. For example, guidelines for health-care providers, including dieticians, highlight the limited research that has been carried out to best identify and treat malnutrition in community dwelling older adults [16].…”
Section: Introductionmentioning
confidence: 99%
“…MOW also provides variation in types of meals provided (hot, chilled or frozen), as well as being able to support special dietary meal requirements, such as texture modified variations. Studies from Australia and other countries have demonstrated that even with the provision of home-delivered meals, some MOW clients still have a poor nutritional status due to their multiple medical and social risk factors [2,3].…”
Section: What's On the Tray? Nutritional Intake Of Meals On Wheels (Mmentioning
confidence: 99%